2017
DOI: 10.1126/scitranslmed.aam6375
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Pompe disease in mice by AAV-mediated liver delivery of secretable acid α-glucosidase

Abstract: Glycogen storage disease type II or Pompe disease is a severe neuromuscular disorder caused by mutations in the lysosomal enzyme, acid α-glucosidase (GAA), which result in pathological accumulation of glycogen throughout the body. Enzyme replacement therapy is available for Pompe disease; however, it has limited efficacy, has high immunogenicity, and fails to correct pathological glycogen accumulation in nervous tissue and skeletal muscle. Using bioinformatics analysis and protein engineering, we developed tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
217
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(232 citation statements)
references
References 71 publications
14
217
1
Order By: Relevance
“…The authors showed in further in vivo experiments that these transgenes, delivered by liver-tropic rAAV, resulted in high levels of secreted GAA, low immunogenicity, and metabolic cross-correction in muscle, central nervous system, and spinal cord. Experiments in nonhuman primates demonstrated the safety of this approach and confirmed that the liver-secreted GAA is efficiently taken up by peripheral tissues [154].…”
Section: Gene Therapy Strategiesmentioning
confidence: 77%
See 1 more Smart Citation
“…The authors showed in further in vivo experiments that these transgenes, delivered by liver-tropic rAAV, resulted in high levels of secreted GAA, low immunogenicity, and metabolic cross-correction in muscle, central nervous system, and spinal cord. Experiments in nonhuman primates demonstrated the safety of this approach and confirmed that the liver-secreted GAA is efficiently taken up by peripheral tissues [154].…”
Section: Gene Therapy Strategiesmentioning
confidence: 77%
“…A more recent preclinical study sought to optimize the liver-directed strategy by testing genetically engineered GAA transgenes (that were codon optimized and contained small deletions within the progene and modified secretion signals) for their ability to be expressed by hepatocytes and produce the highly secretable GAA protein [154]. The authors showed in further in vivo experiments that these transgenes, delivered by liver-tropic rAAV, resulted in high levels of secreted GAA, low immunogenicity, and metabolic cross-correction in muscle, central nervous system, and spinal cord.…”
Section: Gene Therapy Strategiesmentioning
confidence: 99%
“…Studies normalizing glycogen levels solely in the brain and CNS in PD mice (using AAV gene therapy) have shown correction of some neuromuscular phenotypes even in the absence of improvement in cardiac or skeletal muscle fibers, demonstrating that a full reversion of clinical phenotypes in PD ERT will require multisystem delivery 30,31 . While we and others have seen a trend or partial reduction in CNS glycogen storage (Supplementary Figure S9) 27 , it remains unknown whether this reduction will be clinically significant in PD patients. To maximize enzyme delivery to affected tissue types, an effector like CD63, which -in addition to cardiac and skeletal musclesis also expressed in the CNS, would likely be more appropriate than more tissue-restricted internalizers like ITGA7.…”
Section: Conceptually Any Transmembrane or Cell Surface Protein Thatmentioning
confidence: 62%
“…α-hCD63huSC:GAA has higher glycogen removal at equivalent serum levels compared to GAA To determine whether the superior efficacy of α-hCD63SC:GAA is due to both improved targeting as well as improved secretion of α-hCD63SC:GAA compared to GAA (Figures 2A, 2B, and S8), or to primarily only one of these factors, we used a GAA construct that has several modifications to improve expression and secretion. In this construct, AAV-LSP2 GAA 27 , the most notable change is a replacement of the endogenous signal peptide with a chymotrysinogen B2 signal peptide. Additionally, in our α-hCD63SC:GAA construct we changed the scFv to fully human α-hCD63 variable domains (α-hCD63huSC:GAA), as a fully human protein is desirable for possible translation to human trials.…”
Section: Levelsmentioning
confidence: 99%
“…The ultimate goal of such viral gene therapy is to restore production of the functional protein for sustained periods. For those IEMs in which the corrected proteins should be either secreted by or expressed in easily transduced cells (eg, hepatocytes), gene therapy would indeed provide a realistic cure if the transgene insertion could be targeted to harmless sites in the genome. However, when using conventional viruses, the lack of integration control may cause insertional mutagenesis and consequently severe side effects such as cancer.…”
Section: Overview Of the Advantages And Disadvantages Of Different Gementioning
confidence: 99%